Study on the mechanism and control of strong ground pressure in the mining of shallow buried close-distance coal seam passing through the loess hilly region - Yanpeng He; Qingxiang Huang; Li Ma (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract Shallow buried close-distance coal seam (SBCCS) is widely found in northern Shaanxi, China. In the process of mining under the loess hilly area (LHA) in SBCCS, many accidents of strong ground pressure have occurred. Taking the in the Zhangjiamao Coal Mine as the background, this study revealed the mechanism of high ground pressure when the working face of lower coal seam passes through the surface loess hilly region. On-site measurements, physical similarity simulation, numerical calculation, and theoretical analysis were combined to study the mining process of SBCCS. The movement characteristics of the activated structure of the interval strata of the lower coal seam were analyzed. The dynamic load and the change pattern of the front abutment pressure (FAP) of the support during the loading stage of entering and exiting the loess hilly were determined. A coupled structural mechanics model of the overlying activated voussoir beam and the step voussoir beam rock beam of the interval strata was established, revealing the dynamic loading mechanism of strong ground pressure during passing through the LHA. The results showed that the dynamic load of the working face was the highest in areas affected by the load of the LHA, followed by the load while entering the LHA, the peak value of the FAP in the load-influenced LHA was high, which was approximately 1.12 times that after leaving the load-influenced LHA and 1.61 times that before entering this area. By establishing a mechanical model of the roof coupling structure when entering and exiting the load-influenced LHA, it was revealed that the dynamic load of the support while mining under the goaf in the LHA is mainly due to the synchronous movement of the activated structure of the collapsed roof of the upper coal seam and the interval rock structure. The load in the LHA was transmitted to the interval rock structure through the activated structure, resulting in a high dynamic load on the support. The study concluded that the determination of the support resistance of the working face should be based on the high-period compressive load of the synchronous movement of the roof structure in the LHA. Through the engineering practice of hydraulic fracturing, the roof structure of the interval strata is changed, which can effectively reduce the dynamic pressure disaster of the working face. The research provides a scientific basis for the safe and efficient mining of shallow coalfields, and it provides reference for similar mining.